Perspektywa oceniania a spostrzegana atrakcyjność twarzy autentycznych: różnice międzypłciowe = The perspective of judgements and the perception of facial attractivness natural: gender differences - Gawron, Dagmara (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article concerns the differences in the perception of facial attractiveness natural and modification depending on the perspective of judgements and gender. In the experiment (N = 233), a natural facial photo was rated three times. The first was self-rating by the participant. The second was by an observer. The third was the looking glass self. The results showed that participants rated themselves better than observers. But the perspective of the looking glass self was better than the observer's perspective, but worse than the perspective of self.
Keywords: atrakcyjność twarzy; preferencje estetyczne; różnice międzypłciowe; faces; attractiveness judgment; gender